2017
DOI: 10.1038/srep44355
|View full text |Cite
|
Sign up to set email alerts
|

A significant net sink for CO2 in Tokyo Bay

Abstract: Most estuaries and inland waters are significant source for atmospheric CO2 because of input of terrestrial inorganic carbon and mineralization of terrestrially supplied organic carbon. In contrast to most coastal waters, some estuaries with small freshwater discharge are weak source or sometimes sink for CO2. Extensive surveys of pCO2 in Tokyo Bay showed that the overall bay acts as a strong net sink for atmospheric CO2. Although small area was a consistent source for CO2, active photosynthesis driven by nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 35 publications
4
41
0
Order By: Relevance
“…[71][72][73] Theoretically, reduced skin barrier in AD and presence of FLG mutations would increase the levels of allergens penetrating across the SC and hence the risk of ACD. Consistently Kubo et al [74] showed that trivalent chromium, a potent contact allergen penetrated the filaggrin-deficient murine SC more easily than normal mouse skin. Specifically for nickel, it has been hypothesized that reduced levels of filaggrin would lead to larger amounts of nickel that penetrate the skin due to its ability to bind to histidine, an abundant amino acid and a degradation product of filaggrin.…”
Section: Impaired S Kin Barrier a S A Ris K Fac Tor For Contac T Dementioning
confidence: 53%
“…[71][72][73] Theoretically, reduced skin barrier in AD and presence of FLG mutations would increase the levels of allergens penetrating across the SC and hence the risk of ACD. Consistently Kubo et al [74] showed that trivalent chromium, a potent contact allergen penetrated the filaggrin-deficient murine SC more easily than normal mouse skin. Specifically for nickel, it has been hypothesized that reduced levels of filaggrin would lead to larger amounts of nickel that penetrate the skin due to its ability to bind to histidine, an abundant amino acid and a degradation product of filaggrin.…”
Section: Impaired S Kin Barrier a S A Ris K Fac Tor For Contac T Dementioning
confidence: 53%
“…Just before and/or during these winter blooms in 2010-2011 and 2013, northwest-ward currents were intermittently recorded by continuous observations at the surface off Jogashima Island, Miura (Shiro Toida, Kanagawa Prefectural Fisheries Technology Center, personal communication). Thus, the apparent winter blooms could be induced by the expansion of neighboring Tokyo Bay Water (Furushima & Sugimoto 1995, Ara & Hiromi 2008, Ara et al 2011b, which would contain a much higher phytoplankton standing crop (Chl-a) all year round (Han & Furuya 2000, Kubo et al 2017.…”
Section: Seasonal Variations In Nutrients Chl-a and Phytoplankton Bimentioning
confidence: 99%
“…Other studies such as the New River Estuary however have suggested increased nutrient supplies promote ecosystem heterotrophy (Caffrey, ; Crosswell et al, ; Gazeau et al, ; Valiela, ). This study of the Sydney Harbour Estuary showed that the carbon budget was slightly heterotrophic; however, under conditions of high rainfall, which exposed the middle and lower estuary to anthropogenic nutrient enrichment (Jeffries et al, ), an increase in production transitioned the system to net ecosystem autotrophy (Kubo et al, ; Oviatt et al, ; Vlahos & Whitney, ). Over an annual cycle, the Sydney Harbour estuary was found to be a net exporter of DIC and importer of OC with NEM as the main control on carbon fluxes in the system.…”
Section: Resultsmentioning
confidence: 99%